Kajian Penggunaan Carbon Black N990 sebagai Bahan Pengisi Kompon Karet Alam: Sifat Dinamik, Kestabilan Termal, dan Ketahanan Panas - Adi Cifriadi; Purwantiningsih Sugita; Tetty Kemala; Siti Nikmatin (Jurnal Riset Kimia, 2023)
The manufacture of vibration damping material from natural rubber (NR) required an increase in dynamic properties, thermal stability, and resistance to heat. Using the Carbon Black N990 as a filler in NR vulcanizates can potentially increase on these properties. This research aims to study the effect of using Carbon Black N990 on dynamic properties, thermal stability, and aging resistance to heat in NR vulcanizates. The dynamic properties of NR vulcanizates were determined by Rubber Process Analyzer (RPA), while the thermal stability properties were studied by TGA, and heat resistance was determined by the thermal aging test. The RPA test results showed that adding 50 phr Carbon Black N990 in the NR compound could increase the value of the complex shear modulus to 65%. Furthermore, the results of the TGA test showed that the thermal stability properties of unfilled NR vulcanizates were better than that of NR vulcanizates containing Carbon Black N990. Unfilled NR vulcanizates were heat stable up to 353oC, while NR vulcanizates containing 15, 30, and 50 parts per hundred rubber (phr) Carbon Black N990, respectively, were heat stable up to 348.1oC, 348oC, and 349oC. Based on the requirements of ISO 4632-1, it showed that the NR compound containing Carbon Black N990 has good heat resistance properties. The NR compound formula contains 30 phr Carbon Black N990 showing good dynamic properties and heat resistance in accordance with EN 15129 requirements so that it has the potential to be used as a vibration damping material for earthquake-resistant structures.